2004
DOI: 10.1172/jci19846
|View full text |Cite
|
Sign up to set email alerts
|

Nkx2-5 mutation causes anatomic hypoplasia of the cardiac conduction system

Abstract: Heterozygous mutations of the cardiac transcription factor Nkx2-5 cause atrioventricular conduction defects in humans by unknown mechanisms. We show in KO mice that the number of cells in the cardiac conduction system is directly related to Nkx2-5 gene dosage. Null mutant embryos appear to lack the primordium of the atrioventricular node. In Nkx2-5 haploinsufficiency, the conduction system has half the normal number of cells. In addition, an entire population of connexin40 -/connexin45 + cells is missing in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 219 publications
(122 citation statements)
references
References 38 publications
12
110
0
Order By: Relevance
“…Mutations in two genes, the cardiac sodium channel gene SCN5A on chromosome 3p21 and a cardiac transcription factor gene NKX2.5 on 5q34, were identified in some patients with cardiac conduction disease [27][28][29] . Thus, we first determined whether the Chinese family was linked to one of these two genes by linkage analysis with markers D3S1277 and D5S400.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in two genes, the cardiac sodium channel gene SCN5A on chromosome 3p21 and a cardiac transcription factor gene NKX2.5 on 5q34, were identified in some patients with cardiac conduction disease [27][28][29] . Thus, we first determined whether the Chinese family was linked to one of these two genes by linkage analysis with markers D3S1277 and D5S400.…”
Section: Resultsmentioning
confidence: 99%
“…However, the possibility that dominant negative effects, modifying alleles or environmental factors contribute to other phenotypes cannot be completely excluded because of the small sample size per mutation. Resolution of these questions will require careful analysis in experimental models permitting tight dosing control of NKX2.5 wild-type and mutant proteins [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Nkx2-5-deficient mice showed that Nkx2-5 insufficiency perturbs the conduction system during development, resulting in hypoplasia of the atrioventricular node, the His bundle, and the Purkinje system, and that it manifests as a postnatal conduction defect. 21,22 Taking that report into account, and because of the relatively small size of the NKX2-5 gene, mutation screening was performed in 1 patient from each study family. Searching for mutations within the NKX2-5 gene failed to reveal sequence alterations.…”
Section: Discussionmentioning
confidence: 99%